Deriving disability weights for the Netherlands: findings from the Dutch disability weights measurement study - Juanita A. Haagsma; Periklis Charalampous (BMC, 2024)
Abstract Background The aims of this study were to establish national disability weights based on the health state preferences of a Dutch general population sample, examine the relation between results and respondent's characteristics, and compare disability weights with those estimated in the European disability weights study. Methods In this cross-sectional study, a web-based survey was administered to a general population 18-75 years from the Netherlands. The survey included paired comparison questions. Paired comparison data were analysed using probit regression and located results onto the 0-to-1 disability weight scale using non-parametric regression. Bootstrapping was used to estimate 95% uncertainty intervals (95%UI). Spearman's correlation was used to investigate the relation of probit regression coefficients between respondent's characteristics. Results 3994 respondents completed the questionnaire. The disability weights ranged from 0.007 (95%UI: 0.003-0.012) for mild distance vision impairment to 0.741 (95% UI: 0.498-0.924) for intensive care unit admission. Spearman's correlation of probit coefficients between sub-groups based on respondent's characteristics were all above 0.95 (p < 0.001). Comparison of disability weights of 140 health states that were included in the Dutch and European disability weights study showed a high correlation (Spearman's correlation: 0.942; p < 0.001); however, for 76 (54.3%) health states the point estimate of the Dutch disability weight fell outside of the 95%UI of the European disability weights. Conclusions Respondent's characteristics had no influence on health state valuations with the paired comparison. However, comparison of the Dutch disability weights to the European disability weights indicates that health state preferences of the general population of the Netherlands differ from those of other European countries.